Effect of Growth Hormone Treatment on Quality of Life in Japanese Children with Growth Hormone Deficiency: An Analysis from a Prospective Observational Study - Tanaka, Toshiaki (The Japanese Society for Pediatric Endocrinology, 2014)
The aim of this study was to assess changes in quality of life (QoL) in Japanese children with GH deficiency (GHD) after 12 mo of GH treatment or with idiopathic short stature (ISS) after 12 mo without treatment. Children with GHD were treated with GH after enrollment. Outcome measures included the parent-rated Child Behavior Checklist (CBCL), the Youth Self-Report Form (YSR), and height standard deviation scores (SDS). Total CBCL scores significantly decreased in children with GHD (n = 152, mean change (standard deviation [SD]) = –3.42 [11.21]) and ISS (n = 129, mean change = –4.82 [10.09]) after 12 mo (p < 0.001). Total YSR scores (mean change = –9.21 [14.07]) and height SDS (mean change = 0.35 [0.38]) significantly decreased in children with GHD (p < 0.001), but were unchanged in children with ISS. The change in total YSR score was significantly correlated with the change in height SDS in children with GHD (r = –0.516, p = 0.003). Our findings demonstrate that GH treatment can improve QoL in Japanese children with GHD. The correlation between the changes in total YSR score and height SDS demonstrated that increased height resulted in improved QoL.